Effect of addition of l‐carnitine to cryopreservation extender on rabbit post‐thaw semen parameters, antioxidant capacity, mitochondrial function, apoptosis and ultrastructure changes - Abdelnour, Sameh A.; Hassan, Mahmoud A.E.; El‐Ratel, Ibrahim T.; Essawi, Walaa M.; El‐Raghi, Ali Ali; Lu, Yangqing; Sheiha, Asmaa M. (Reproduction in domestic animals, 2022)
l‐Carnitine (LC) is considered to be a natural antioxidant agent that could be used to improve the efficiency of reproduction. However, the precise machinery of the effect of LC supplementation on frozen–thawed rabbit sperm has not been evaluated. Thus, the aim of this study was to evaluate the effect of the addition of LC to a freezing medium on parameters and ultrastructure changes in frozen–thawed rabbit sperm. Rabbit bucks (7 months of age) were involved, and semen was collected using the artificial vagina method. Pooled rabbit semen was cryopreserved in a tris yolk fructose extender without any supplement (LC0, control group) or with LC at levels of 1, 2 or 4 mM (LC1, LC2 and LC4, respectively). The samples were then loaded into 0.25‐ml straws and frozen over liquid nitrogen vapours before being plunged into the liquid nitrogen and stored at −196°C until evaluation. Data showed that the addition of LC significantly increased sperm motility, viability and membrane function, while sperm abnormalities decreased (p < .001). Sperm‐like apoptosis (early, late and necrosis spermatozoa) was lower in the LC4 group compared with the other groups. l‐Carnitine addition significantly enhanced the total antioxidant capacity and superoxide dismutase and glutathione peroxide activities and significantly reduced the protein carbonyl and malondialdehyde levels compared with the control group. Moreover, electron microscopy images demonstrated that LC addition (2 or 4 mM) preserved the acrosome and plasma membrane and protected the ultrastructure integrity of the cryopreserved spermatozoa in relation to the control group. Spermatozoa treated with LC exhibited higher mitochondria membrane potential (MMP) values compared with the control group. We conclude that the addition of LC (4 mM) to the freezing extender enhanced the quality, increased the antioxidant capabilities, preserved the ultrastructure integrity and reduced lipid and protein peroxidation as well as increased MMP activity of frozen–thawed rabbit sperm.